The Structure Of Chemical Concepts Among Students Of The Faculty Of Education Of Pure Sciences / Ibn Al-Haitham (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the structure of chemical concepts in the students of the Faculty of Education of Pure Sciences / Ibn al-Haytham and used the descriptive method, to suit the nature of the research goal and to verify this was built testing the structure of chemical concepts consisting of (12) conceptual paragraphs (map) distributed to four questions analyzed data and statistically treated using (t-test) for two independent samples, equivalent Cooper, difficulty coefficient equation, discrimination coefficient equation, Pearson correlation coefficient, Quidor and Richardson equation (20), alpha-Cronbach equation, and the following results were reached: the level of performance of fourth-graders - chemistry department in the Faculty of Education for Pure Sciences / Ibn Al-Haytham was high in testing the structure of chemical concepts, and there are no statistical function differences attributable to the sex variable in the test of the structure of chemical concepts.